2014
DOI: 10.1063/1.4874875
|View full text |Cite
|
Sign up to set email alerts
|

Vapor liquid solid-hydride vapor phase epitaxy (VLS-HVPE) growth of ultra-long defect-free GaAs nanowires: Ab initio simulations supporting center nucleation

Abstract: High aspect ratio, rod-like and single crystal phase GaAs nanowires (NWs) were grown by gold catalyst-assisted hydride vapor phase epitaxy (HVPE). High resolution transmission electron microscopy and micro-Raman spectroscopy revealed polytypism-free zinc blende (ZB) NWs over lengths of several tens of micrometers for a mean diameter of 50 nm. Micro-photoluminescence studies of individual NWs showed linewidths smaller than those reported elsewhere which is consistent with the crystalline quality of the NWs. HVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…Using the recommended value of A = 7 nm –2 s –1 at T ≅ 600 °C of ref , we deduce the diffusion coefficient of As in liquid Ga: D 5 = 2 × 10 –12 m 2 /s at this temperature. Interestingly, this is 3 orders of magnitude smaller than the diffusion coefficient of Ga in liquid Au at T = 715 °C under the assumption of c 3 = 0.2, estimated in ref . Such a huge difference could be only partly due to a higher temperature and/or different metal vehicles and supports our assumption that As is generally a much slower diffuser compared to Ga.…”
Section: Theoretical Analysissupporting
confidence: 80%
“…Using the recommended value of A = 7 nm –2 s –1 at T ≅ 600 °C of ref , we deduce the diffusion coefficient of As in liquid Ga: D 5 = 2 × 10 –12 m 2 /s at this temperature. Interestingly, this is 3 orders of magnitude smaller than the diffusion coefficient of Ga in liquid Au at T = 715 °C under the assumption of c 3 = 0.2, estimated in ref . Such a huge difference could be only partly due to a higher temperature and/or different metal vehicles and supports our assumption that As is generally a much slower diffuser compared to Ga.…”
Section: Theoretical Analysissupporting
confidence: 80%
“…In this wide range of temperatures, the atomic interdiffusion between the substrate and the catalyst always serves as an additional supply of gallium and should be favorable for the NW nucleation on GaAs substrates. 7,9,18 The picture becomes different when the VLS growth of GaAs NWs takes place on silicon substrates covered/or not with an oxide layer, which is paramount for monolithic integration of III−V photonics with silicon electronic platform. It has been shown that the presence of an oxide layer at the interface between gold and silicon substrate blocks the interexchange between the two materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, gold-catalyzed GaAs NWs on GaAs substrates are grown by MBE at temperatures from 400 to 620 °C (ref ), while gold-catalyzed HVPE GaAs NWs are grown at temperatures higher than 700 °C (refs and ). In this wide range of temperatures, the atomic interdiffusion between the substrate and the catalyst always serves as an additional supply of gallium and should be favorable for the NW nucleation on GaAs substrates. ,, …”
Section: Introductionmentioning
confidence: 99%
“…For Au-assisted VLS growth of GaAs NWs on GaAs substrates, MBE [106][107][108] and MOVPE [109,110] operate at temperatures ranging from 400 to 620°C. HVPE GaAs NWs are grown at temperatures higher than 700 o C. In this wide range of temperatures, the atomic interdiffusion between the substrate and the catalyst always serves as an additional supply of gallium and should be favorable for the NW nucleation on GaAs substrates [106,88].…”
Section: Iii1 Introductionmentioning
confidence: 99%